1999
DOI: 10.1103/physrevlett.83.1163
|View full text |Cite
|
Sign up to set email alerts
|

Burrowing of Co Nanoparticles on Clean Cu and Ag Surfaces

Abstract: Metal nanoparticles can display a unique behavior when deposited on substrates with a significantly lower surface energy. Co nanoparticles in the 10 nm size regime burrow into clean Cu(100) and Ag(100) substrates when deposited at 600 K and also assume the substrate orientation. Deposition at room temperature fails to show either burrowing or reorientation. Crucial in understanding these results are the capillary forces and surface tension associated with a nanoparticle: they must be high enough to drive atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 24 publications
7
59
0
Order By: Relevance
“…This is also in accordance with theoretical calculations of the atomic deposition [24]. Both intermixing as well as capping up to the point of burrowing of the cluster into the surface [25] are enhanced at temperatures well above 300K. Since our samples were prepared at room temperature, only small influences of intermixing are expected, in accordance with the results presented below.…”
Section: Resultssupporting
confidence: 91%
“…This is also in accordance with theoretical calculations of the atomic deposition [24]. Both intermixing as well as capping up to the point of burrowing of the cluster into the surface [25] are enhanced at temperatures well above 300K. Since our samples were prepared at room temperature, only small influences of intermixing are expected, in accordance with the results presented below.…”
Section: Resultssupporting
confidence: 91%
“…The Co/Cu͑100͒ system is further stabilized when the Co atoms form clusters, and when these clusters reside in deeper layer of the substrate. The most recent experiments performed by Zimmermann et al, 24 have found a burrowing of Co nanoparticles in Cu substrate. This finding is in line with our main results.…”
Section: ͑4͒mentioning
confidence: 94%
“…Recently, a strong impetus has been given to studies of nanocluster/nanostructured thin layers for two main reasons. [1][2][3][4][5][6] The first stems from the demand of miniaturization of electronic devices. Specifically, one would like to grow well-organized nanometer-size islands with specific electronic properties.…”
mentioning
confidence: 99%